Prevalence and Risk Factors of Diabetic Retinopathy in Type 2 Diabetic Patients Attending Tertiary Care Hospitals in Punjab: Diabetic Retinopathy in Punjab: Prevalence and Risk Factors - Waheed, Mustafa Khalid; Tahir, Muhammad Ibrahim; Sada, Sadaf; Imran, Amna; Nadeem, Saleha; Talha, Muhammad (DEVELOPMENTAL MEDICO-LIFE-SCIENCES, 2025)
Background: Diabetic retinopathy (DR) is one of the most frequent microvascular consequences of type 2 diabetes mellitus, accounting for a significant portion of avoidable blindness globally. In low- and middle-income countries like Pakistan, where diabetes incidence is growing and regular screening is restricted, DR is a serious public health concern. Objective: The purpose of this research was to assess the prevalence, forms, and risk factors of diabetic retinopathy in patients with type 2 diabetes mellitus treated at tertiary care facilities in Punjab, Pakistan. Methods: A cross-sectional study was carried out from June 2023 to May 2025 at Gulab Devi Hospital and Ghurki Trust Teaching Hospital in Lahore. 70 individuals with confirmed type 2 diabetes were recruited using sequential nonprobability sampling. After pupil dilatation, a fundus examination was conducted using indirect ophthalmoscopy. The clinical and biochemical information collected were age, gender, blood pressure, body mass index (BMI), HbA1c, lipid profile, diabetes duration, and nephropathy indicators. Data were evaluated using SPSS version 25, and p-values < 0.05 were deemed statistically significant. Results: Diabetic retinopathy was seen in 34.3% of individuals (n = 24). Non-proliferative diabetic retinopathy (NPDR) accounted for 62.5% of cases, followed by proliferative diabetic retinopathy (PDR) at 25.0% and diabetic macular edema (DME) at 12.5%. Significant risk variables for DR were diabetes duration > 10 years (p < 0.001), poor glycemic control (HbA1c ≥ 8%; p = 0.010), hypertension (p = 0.036), BMI ≥ 27 kg/m² (p = 0.048), and diabetic nephropathy (p = 0.012). Elevated LDL cholesterol levels were more common among DR patients, but not statistically significant (p = 0.065). Conclusion: Diabetic retinopathy affects a significant number of type 2 diabetes patients at Punjab's tertiary care facilities, often in severe, vision-threatening stages. The most important modifiable risk variables were poor glycemic management, prolonged illness duration, hypertension, obesity, and nephropathy. In Pakistan, regular eye examination, appropriate metabolic management, and early intervention are critical for preventing diabetic retinopathy-related vision loss.